Analysis of aortic area/height ratio in patients with thoracic aortic aneurysm and Type A dissection. (15th March 2018) - Acharya, Metesh Nalin; Youssefi, Pouya; Soppa, Gopal; Valencia, Oswaldo; Nowell, Justin; Kanagasabay, Robin; Edsell, Mark; Morgan, Robert; Tome, Maite; Jahangiri, Marjan
Abstract: OBJECTIVES: Significant proportions of aortic dissections occur at aortic diameters <5.5 cm. By indexing aortic area to height and correlating with absolute aortic diameter, we sought to identify those aneurysm patients with aortic diameters <5.5 cm who do not meet current size thresholds for surgery, yet with corresponding abnormal indexed aortic areas (IAAs) >10 cm 2 /m, are at increased risk of aortic complications. METHODS: IAAs were calculated at 3 aortic locations in 187 aneurysm and 66 dissection patients operated on between 2010 and 2016 at our tertiary aortic centre. Proportions of patients with IAA >10 cm 2 /m, mean IAAs corresponding to aortic diameters <4.0 cm, 4.0–4.5 cm, 4.5–5.0 cm, 5.0–5.5 cm and >5.5 cm, and mean aortic diameters corresponding to IAAs 10–12 cm 2 /m, 12–14 cm 2 /m and >14 cm 2 /m were determined. RESULTS: Proportions of patients with abnormal IAAs were similar in both groups. In all, 49.1% of aneurysm patients with aortic diameters 4.5–5.0 cm, and 98.5% with aortic diameters 5.0–5.5 cm had abnormal IAAs. Out of 200 separate aneurysms with IAAs >10 cm 2 /m between the mid-sinus and mid-ascending aorta, 139 (69.5%) would not warrant surgery according to existing guidelines. CONCLUSIONS: Using the IAA, we identified a significant proportion of patients with thoracic aortic aneurysms who are at increased risk of aortic complications, despite current aortic guidelines not endorsing surgical intervention in this group. Our data suggests the IAA may be useful in preoperative risk evaluation and as a criterion for surgery.